Heart rate deflection point relates to second ventilatory threshold in a tennis test - Baiget, E.; Fernandez-Fernandez, J.; Iglesias, X.; Rodriguez, F. A. (The Journal of Strength and Conditioning Research, 2015)
The relationship between heart rate deflection point (HRDP) and the second ventilatory threshold (VT2) has been studied in continuous sports, but never in a tennis-specific test. The aim of the study was to assess the relationships between HRDP and the VT2, and between the maximal test performance and the maximal oxygen uptake (VO2max) in an on-court specific endurance tennis test. Thirty-five high-level tennis players performed a progressive tennis-specific field test to exhaustion to determine HRDP, VT2, and VO2max. Ventilatory gas exchange parameters were continuously recorded by a portable telemetric breath-by-breath gas exchange measurement system. Heart rate deflection point was identified at the point at which the slope values of the linear portion of the time/heart rate (HR) relationship began to decline and was successfully determined in 91.4% of the players. High correlations (r = 0.79-0.96; p < 0.001) between physiological (HR and oxygen uptake [VO2max]) and performance (Time, Stage, and Frequency of balls [Ballf]) variables corresponding to HRDP and VT2 were observed. Frequency of balls at the HRDP (BallfHRDP) was detected at 19.8 ± 1.7 shots per minute. Paired t-test showed no significant differences in HR (178.9 ± 8.5 vs. 177.9 ± 8.7 b/min for HRDP vs. HRVT2, respectively) at intensities corresponding to HRDP and VT2. Maximal test performance and VO2max were moderately correlated (r = 0.56; p < 0.001). Heart rate deflection point obtained from this specific tennis test can be used to determine the VT2, and the BallfHRDP can be used as a practical performance variable to prescribe on-court specific aerobic training at or near VT2.